Decision support system for choosing the best tourist attractions using simple additive weighting (SAW) method - Nurdin, Alya Aulia (SHM Publisher, 2021)
Every year, various regions in Indonesia always have many tourists both local and foreign so as to provide benefits for the government and the surrounding local community. However, due to the Covid-19 pandemic, the tourism sector has slumped. Therefore, to revive the tourism sector in the new normal due to Covid-19, there needs to be various considerations. One of them, namely decision support system for choosing tourist attractions with facilities that meet health protocol standards in the new normal/adaptation of new habits. In this study, a case was raised with the aim of choosing the best tourist attractions in Kendal Regency, Central Java with several criteria determined, especially regarding facilities that comply with health protocols. The calculation in this study was done by Simple Additive Weighting (SAW) method. The research was conducted by determining alternatives, criteria, and weight values on each criterion. Then the calculation of the value of preferences and stamps to get the best alternative. From the calculations that have been done, the result of the best tourist attractions in Kendal is Tirto Arum Baru with a preference value of 0.766. However, due to the dynamic nature of the criteria and weight data, it is possible that at any time the selected data may change.